Pediatric kidney care experience after the 2023 Türkiye earthquake - Bakkaloglu, Sevcan A.; Delibas, Ali; Doven, Serra Surmeli; Taner, Sevgin; Yavuz, Sevgi; Erfidan, Gokcen; Sever, Lale (Oxford Univ Press, 2024)
Background. Two earthquakes on 6 February 2023 destroyed 10 cities in Turkiye. We report our experience with pediatric victims during these catastrophes, with a focus on crush syndrome related-acute kidney injury (Crush-AKI) and death. Method. Web-based software was prepared. Patient demographics, time under rubble (TUR), admission laboratory data, dialysis, and kidney and overall outcomes were recorded. Results. A total of 903 injured children (median age 11.62 years) were evaluated. Mean TUR was 13 h (interquartile range 32.5, max 240 h). Thirty-one of 32 patients with a TUR of >120 h survived. The patient who was rescued after 10 days survived. Two-thirds of the patients were given 50 mEq/L sodium bicarbonate in 0.45% sodium chloride solution on admission day. Fifty-eight percent of patients were given intravenous fluid (IVF) at a volume of 2000-3000 mL/m(2) body surface area (BSA), 40% at 3000-4000 mL/m(2) BSA and only 2% at >4000 mL/m(2) BSA. A total of 425 patients had surgeries, and 48 suffered from major bleeding. Amputations were recorded in 96 patients. Eighty-two and 66 patients required ventilator and inotropic support, respectively. Crush-AKI developed in 314 patients (36% of all patients). In all, 189 patients were dialyzed. Age >15 years, creatine phosphokinase (CK) >= 20 950 U/L, TUR >= 10 h and the first-day IVF volume <3000-4000 mL/m2 BSA were associated with Crush-AKI development. Twenty-two deaths were recorded, 20 of 22 occurring in patients with Crush-AKI and within the first 4 days of admission. All patients admitted after 7 days survived. Conclusions. These are the most extensive pediatric kidney disaster data obtained after an earthquake. Serum CK level was significantly associated with Crush-AKI at the levels of >20 950 U/L, but not with death. Adolescent age and initial IVF of less than 3000-4000 mL/m(2) BSA were also associated with Crush-AKI. Given that mildly injured victims can survive longer periods in the disaster field, we suggest uninterrupted rescue activity for at least 10 days.
Keywords: acute kidney injury; children; crush syndrome; earthquake; Turkiye